2002
DOI: 10.1103/physrevlett.89.196403
|View full text |Cite
|
Sign up to set email alerts
|

Stripe Phases in the Two-Dimensional Falicov-Kimball Model

Abstract: The observation of charge stripe order in the doped nickelate and cuprate materials has motivated much theoretical effort to understand the underlying mechanism of the stripe phase. Numerical studies of the Hubbard model show two possibilities: (i) stripe order arises from a tendency toward phase separation and its competition with the long-range Coulomb interaction or (ii) stripe order inherently arises as a compromise between itinerancy and magnetic interactions. Here we determine the restricted phase diagra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 42 publications
(28 reference statements)
5
65
0
Order By: Relevance
“…In this case at low temperature the localized particles form patterns which are incommensurate with the underlying lattice [13], which results in a rich structure of the density of states even without magnetic field. The fractal structure of the Hofstadter butterfly is a result of an interplay between two length scales: lattice constant and the Landau radius.…”
Section: Discussionmentioning
confidence: 99%
“…In this case at low temperature the localized particles form patterns which are incommensurate with the underlying lattice [13], which results in a rich structure of the density of states even without magnetic field. The fractal structure of the Hofstadter butterfly is a result of an interplay between two length scales: lattice constant and the Landau radius.…”
Section: Discussionmentioning
confidence: 99%
“…The vertical/horizontal striped phase is closer to the segregated phase than the diagonal striped phase. In case the both kinds of stripe phases (vertical/horizontal and diagonal) appear in a phase diagram, such a succession of striped phases is perhaps generic, see also [15,32].…”
Section: Discussion Of the Phase Diagrams And Conclusionmentioning
confidence: 99%
“…Buhler et al [14] have found, by means of Monte Carlo simulations, that upon hole doping antiferromagnetic spin domains and charge stripes, whose properties are in very good agreement with experiments, appear in a spin-fermion model for cuprates. Using the so called restricted phase diagrams, the stability problem of charge-stripe phases has been studied in the spinless Falicov-Kimball model by Lemanski et al [15,16]. In their study the formation of charge stripe-ordered phases can be looked upon as a way the system interpolates between a periodic charge-density wave phase (the chessboard phase) and the segregated phase (a mixture of completely filled and completely empty phases), as the degree of doping varies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations